FOAMING CAN REDUCE LUBRICATION OF LUBRICANTS SO CAUSING WEAR - Rona Malam Karina; M Hanifuddin; Setyo Wibowo (Testing Center for Oil and Gas LEMIGAS, 2018)
Foaming on oil has a very undesirable effect which can cause an increase in oxidation by intensive mixture with air, damage to cavitation, and insufficient oil transportation in the lubrication circulation system which can cause poor lubrication. Adding the appropriate antifoam additives is one way to avoidfoaming. To determine the tendency of foaming formation which has an impact on the stability of the performance of lubricating oil, so that there is wear and tear in research in the laboratory by means of; 6 types of lubricating oil taken from the market are tested for viscosity, index viscosity, flash point, pour point and color. As well as to determine the effect of foam formation tested foaming tendency / stability and wear before and after antifoam added from 6 (six) types of lubricated oil obtained from the market. The result after adding antifoam additives, three types (GB, SH, and MH) of six types of lubricated oil were tested, the tendency of foaming and the wear results met the required limits, namely 0/50/0 ml for foaming tendency and maximum 0.5 mm for wear, while for 3 (three) oils, the results are not satisfying the required limits.